THE EFFECT OF MACRO FACTORS ON BANK CREDIT ACTIVITY IN THE REPUBLIC OF SERBIA - Živkov, Dejan; Poparić, Simo; Ilić, Miloš (International Journal of Economic Practice and Policy, 2021)
This paper investigates whether and how key macro-fundamentals in Serbia affect the volumes of issued loans of Erste bank to civil sector and enterprises in Serbia. We put an effort to determine which particular macro factor has the highest influence on issued credits of Erste bank, and to measure the exact average magnitude of these influences. The main idea is to find out how GDP, inflation, central bank referent interest rate, exchange rate changes and Euribor affect short-term and long-term credit activity of Erste bank in Serbia. The computations are done by applying several multivariate regression models. We can report that Euribor is the most important factor of all scrutinized macro-aggregates, since it affects most of the analysed bank loans. Besides Euribor, we find that other macro fundamentals influence the issued loans only sporadically. In other words, the level of GDP and inflation affect only long-term loans for enterprises, while referent interest rate has an influence only on short-term loans for civil population. Somewhat unexpected, we find that exchange rate changes have no effect on any loan of Erste bank, whatsoever, which clearly indicates that the bank protects itself very successfully against this type of macro risk.